alpha-synuclein metabolism and aggregation is linked to ubiquitin-independent degradation by the proteasome. - Tofaris, G; Layfield, R; Spillantini, MG (2001)
alpha-Synuclein has been implicated in the pathogenesis of Parkinson's disease based on mutations in familial cases of the disease and its presence in Lewy bodies. Here we show that over-expression of wild-type human alpha-synuclein is sufficient to induce inclusion formation in SH-SY5Y cells. In this cellular model, proteasome inhibition leads to an increase of alpha-synuclein accumulation in vivo without ubiquitylation. In accordance, we find that in vitro, unmodified alpha-synuclein can be directly degraded by the 20S proteasome. These findings suggest an ubiquitin-independent mechanism of proteasomal degradation for alpha-synuclein and other natively unfolded proteins.